P291 Pharmacokinetics, safety, and tolerability of etrasimod (APD334) in subjects with mild, moderate, or severe hepatic impairment: a single-dose, open-label, parallel-group study. (27th May 2021) - Lee, C; Tang, Y; Schroeder, C; Zhang, J; Nguyen-Cleary, T; Mullin, S; Ma, M; Lyon, N; Grundy, J
Abstract: Background: Etrasimod is an oral, selective sphingosine 1-phosphate receptor modulator in clinical development for immune-mediated inflammatory disorders, including ulcerative colitis, Crohn's disease, and eosinophilic esophagitis. The objective of this study was to evaluate the effect of hepatic impairment on the pharmacokinetics (PK), safety, and tolerability of etrasimod. Methods: This single-dose, open-label, parallel-group study included 36 adult subjects (aged 18-80 years; body mass index ≥18 kg/m 2 ) with hepatic impairment, based on Child-Pugh score at screening (mild=5 to 6 [n=8], moderate=7 to 9 [n=8], severe=10 to 14 [n=6]), and their demographically matched control subjects with normal hepatic function (n=14 total). The first subject with severe hepatic impairment was enrolled after ≥2 subjects with mild and ≥2 subjects with moderate hepatic impairment had been enrolled and followed for ≥48 hours after dosing to ensure no observed significant safety signals. On Day 1, subjects received a single oral dose of etrasimod 2 mg after a ≥10 hour fast. PK and safety data were collected over a 21-day follow-up period. Results: Thirty-six subjects were enrolled and dosed; 35 subjects completed the study. When compared with their respective demographically matched normal control groups, single dose etrasimod peak exposure (Cmax ) was comparable for all hepatic impairment groups, whereas etrasimod total exposure (AUC) measures were progressively higher (up to 57.3% higher) in the mild, moderate, and severe hepatic impairment groups (Table 1 ). Unbound etrasimod Cmax values were progressively lower (up to 42.0% lower) in the mild, moderate, and severe hepatic impairment groups, whereas unbound etrasimod AUC values were typically comparable for all hepatic impairment groups, when compared with their respective demographically matched normal control groups (Table 2 ). Etrasimod t1/2 only moderately increased as hepatic function decreased, with mean values ranging from 43.9 to 59.5 hours in the demographically matched normal control groups and mean values of 55.7, 69.7, and 76.5 hours in the mild, moderate, and severe hepatic impairment groups, respectively. A single oral dose of etrasimod 2 mg was well tolerated; there were no clinically significant safety findings when administered to subjects with normal hepatic function or subjects with mild, moderate, or severe hepatic impairment. Conclusion: A single oral dose of etrasimod 2 mg was well tolerated, with relatively modest changes in etrasimod exposure observed in subjects with mild, moderate, or severe hepatic impairment. These results suggest that etrasimod dose adjustment may not be warranted in subjects with hepatic impairment.